The minuses : poems - Macarty, Jami (Mountain west poetry series., 2020)
"The Minuses invites us into borderlands battlegrounds between the myriad forms of domination and resistance. Desert, coasts, and interpersonal boundaries provide both context and figure. Destructive nor'easters pummel shorelines. The desert "waxes, waxes," continuing to exert itself. The population of raptor and carrion birds-owls, ravens, and vultures-increases, as human beings abuse one another and themselves under the aegis of patriarchy. Conjuring the literature of the desert, such as If There Were Anywhere But Desert by Egyptian-French writer and poet Edmond Jabès (translated by Rosmarie Waldrop), Desert Solitaire by American writer Edward Abbey, and Land of Little Rain by American writer Mary Austin, Jami Macarty's collection beckons attention to ecological and feminist issues and the co-incidence of eating disorders, sexual harassment, family violence, intimate-partner violence, homelessness, suicide, urban encroachment, endangered species, and other forms of disrespect and distress. Split and multi-perspective speakers claim voice from abusive relationships, dysfunctional families, gun deaths, as contemplators of natural splendors, and as seekers of incarnate desires. Multiple speakers amplify the endangerments predicating women's lives and the natural world, laying bare the struggle and faith necessary to endure with integrity and spirit intact. An aesthetic of eco-feminism defines The Minuses. The poems edge contained space, seeking pathways out of confinement created by relationship, danger, belief, and self. Each poem invites reflective emersion in the objects they contemplate. Through use of catalogue and the elliptical, Macarty activates "what's left open," catalyzing meditation upon the gaps, the missing, the elusive tension between background and foreground. These poems court reader engagement with the liminal, where the lyric meets language, linear narrative meets fragment, and certainty meets ambiguity. Welcome to the borderlands between definition and abstraction, between nature and innovation, between our aspiring selves and the weighty mandates of the patriarchy"--